Mackenzie pipeline hearings, Hyatt Regency - Justice Berger - Pacific Tribune (photographer) (1976)
Hearings conducted by the Berger Inquiry into the Mackenzie Valley Pipeline opened in Vancouver May 10, 11 and 12 before moving to Calgary. Photograph shows Inquiry Commissioner Justice Tom Berger